Sonic explorations of the southernmost continent: four composers' responses to Antarctica and climate change in the twenty-first century - Philpott, C (Organised Sound, 2016)
Composers have been drawn to the worlds southernmostcontinent, Antarctica, for creative inspiration since theso-called Heroic Age of Antarctic Exploration in the latenineteenth and early twentieth centuries. However, it hasonly been since the final few years of the twentieth centurythat professional composers have had opportunities to travelto the far south as part of arts residency programmes toexperience its environment and its unique soundscapes first-hand. Most composers who have visited Antarctica todate have utilised sound recording technologies to documenttheir journeys sonically and have subsequently createdcompositions that feature their soundscape recordings.Typically, such compositions include biological sounds, suchas vocalisations of penguins and seals (both on the ice andunderwater); non-biological or geophysical ambient soundsthat emanate from the natural landscape, such as those createdby wind, blizzards, and ice cracking and calving; and/oranthropogenic (human) sounds recorded within the Antarcticenvironment.This article examines a series of recent compositions byfour established composers who have visited Antarcticaand used their experiences and field recordings to informtheir creative work: Douglas Quin, Jay Needham,Lawrence English and Philip Samartzis. The primary aimof this research is to investigate what these composersAntarctica-related works reveal about their individualencounters with and perceptions of the frozen continent,as well as to consider the role of such compositions inconveying messages related to climate change to listenersaround the globe the vast majority of whom are unlikelyto ever see or hear the place in person.